Uterine artery embolisation or myomectomy for women with uterine fibroids wishing to avoid hysterectomy: a cost–utility analysis of the FEMME trial. (5th July 2021) - Rana, D; Wu, O; Cheed, V; Middleton, LJ; Moss, J; Lumsden, M‐A; McKinnon, W; Daniels, J; Sirkeci, F; Manyonda, I; Belli, A‐M; McPherson, K; et al.
Abstract : Objectives: To assess the cost‐effectiveness of uterine artery embolisation (UAE) and myomectomy for women with symptomatic uterine fibroids wishing to avoid hysterectomy. Design: Economic evaluation alongside the FEMME randomised controlled trial. Setting: 29 UK hospitals. Population: Premenopausal women who had symptomatic uterine fibroids amenable to UAE or myomectomy wishing to avoid hysterectomy. 254 women were randomised to UAE (127) and myomectomy (127). Methods: A within‐trial cost–utility analysis was conducted from the perspective of the UK NHS. Main outcome measures: Quality‐adjusted life years (QALYs) measured using the EuroQoL EQ‐5D‐3L, combined with costs to estimate cost‐effectiveness over 2 and 4 years of follow‐up. Results: Over a 2‐year time horizon, UAE was associated with higher mean costs (difference £645; 95% CI −1381 to 2580) and lower QALYs (difference −0.09; 95% CI −0.11 to −0.04) when compared with myomectomy. Similar results were observed over the 4‐year time horizon. Thus, UAE was dominated by myomectomy. Results of the sensitivity analyses were consistent with the base case results for both years. Over 2 years, UAE was associated with higher costs (difference £456; 95% CI −1823 to 3164) and lower QALYs (difference −0.06; 95% CI −0.11 to −0.02). Conclusions: Myomectomy is a cost‐effective option for the treatment of uterine fibroids. The differences in costs and QALYs are small. Women should be fully informed and have the option to choose between the two procedures. Tweetable abstract: Fully informed women with uterine fibroids should have a choice between uterine artery embolisation or myomectomy. Tweetable abstract: Fully informed women with uterine fibroids should have a choice between uterine artery embolisation or myomectomy.